Socio-Economic Consequences and Mitigation Strategies of the COVID-19 Pandemic (Phases One and Two) on Rural Farmers in Ebonyi State, Nigeria - Justin Kelechi Nmerengwa (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
This study assessed the socio-economic consequences and mitigation strategies of the COVID-19 pandemic (phases one and two) on rural farmers in Ebonyi State, Nigeria. Specifically, the study described the socio-economic characteristics of rural farmers, assessed the perceived socio-economic consequences of the COVID-19 pandemic, and identified strategies used by farmers to cope with the effects of the COVID-19 pandemic. A multistage random sampling technique was employed to select 120 respondents from whom data were collected using a semi-structured questionnaire. Data collected were analysed using descriptive statistics and a mean score. The results showed that disruption in children's education ( =3.02), reduced purchasing power and increased rate of inflation across the country ( =2.83), a reduction in diversity and amount of food consumed ( =2.77), a reduction in the standard of living ( =2.68), a reduction of farm income ( =2.63), reduced off-farm employment and income ( =2.61), loss of lives ( =2.61), an increase in prices of food items ( =2.59), reduced religious activities and gatherings ( =2.57), reduction of remittance ( =2.54) and high foreign exchange rates ( =2.53) were some of the perceived socio-economic consequences of the pandemic. Meanwhile, 80.00% and 70.83% of the rural farmers reduced the quantity of meals eaten and prayed to God, respectively. It was recommended that government assistance programmes must be modified and augmented in order to better reach rural populations, many of whom do not have access to formal contributory social insurance systems.